Catalogue of introduced and local banana cultivars in the Philippines: Results of a demonstration trial by the Institute of Plant Breeding, University of the Philippines, Los Baños - Cruz, F.S. de la; Gueco, L.S.; Damasco, O.P.; Huelgas, V.C.; Banasihan, I.G.; Lladones, R.V.; Bergh, Inge van den; Molina, A.B. (2007)
This catalogue provides information on the morphological and yield characteristics of 19 introduced and 8 local banana cultivars grown at the IPB-UPLB demonstration plot. It is intended to serve as a guide to help in identifying and selecting cultivars for further evaluation by researchers and planting by interested growers.